The Development of Guided Inquiry Learning Model Based on Islamic Values in Islamic Education Courses - Lilis Sholihah; Aan Hasanah; Hariman Surya Siregar; Nurhamzah Nurhamzah; Fuad Fazil Osmanov (International Journal of Islamic Educational Research, 2025)
Islamic education learning models in campus environments often face challenges in integrating critical thinking with religious character building. Dogmatic and lecturer-centered learning makes students less involved in discovering contextual religious meaning. This study aims to explore the development of an Islamic value-based Guided Inquiry learning model in Islamic education courses. The research method used is Research and Development (R&D) with an adaptation of the Thiagarajan, Semmel & Semmel model using the 4D approach (Define, Design, Develop, Disseminate), as well as a combination of quantitative and qualitative methods (mixed methods) through tests, questionnaires, observations, interviews, and reflective journals. Quantitative analysis used a mean difference test. The results showed that the developed model consisted of eight phases, namely Open, Immerse, Explore, Identify, Gather, Create, Share, and Evaluate, which were integrated with Islamic values, such as faith, honesty, responsibility, and tolerance. Expert validation showed high feasibility, namely 93.33%. The implementation in the student classroom showed the feasibility of the model syntax with an average observation score of 87.4%, with the Open and Share phases being the most consistent. Empirically, the developed model was effectively implemented in PAI learning with an increase in the average score in meeting I from 58.24 to 73.23, in meeting II from 66.17 to 84.5, and in meeting III, the average score increased from 55.34 to 81.78. The developed model had a very strong impact on shaping student behavior, as shown by the questionnaire results with a score of 93.48%. Supporting factors included the learning environment (with an influence score of 4.55), lecturers and teaching methods (influence score of 4.78), students (influence score of 4.19), and curriculum and material factors (score of 4.37). This means that these factors were identified as factors influencing the development of the learning model.